2021
DOI: 10.1097/rlu.0000000000003793
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Colitis Mimicking Malignancy on 68Ga-FAPI PET/CT

Abstract: A 40-year-old man presented with abdominal pain and diarrhea for 2 months. Abdominal CT showed thickening of the cecal wall, which was considered likely malignant. The patient was subsequently enrolled in a clinical trial of 68 Ga-FAPI PET/CT study in tumors. Intense 68 Ga-FAPI activity was noted in the thickened cecum, also suggestive of malignancy. However, pathological examination from biopsy rendered a diagnosis of chronic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…68 Ga-DOTA-FAPI-04 is a novel PET agent that has been shown to be promising for imaging tumors 5,6 . In addition, 68 Ga-DOTA-FAPI-04 in multiple inflammatory lesions including tuberculosis, 7 arthritis, 8 chronic colitis, 9 esophagitis, 10 thyroiditis, 11 organizing pneumonia, 12 immunoglobulin G4–related disease, 13 SAPHO syndrome, 14 and dermatomyositis 15 has also been reported. In our case, 68 Ga-DOTA-FAPI-04 uptake was significantly increased in radioactive iodine–induced chronic parotitis.…”
mentioning
confidence: 99%
“…68 Ga-DOTA-FAPI-04 is a novel PET agent that has been shown to be promising for imaging tumors 5,6 . In addition, 68 Ga-DOTA-FAPI-04 in multiple inflammatory lesions including tuberculosis, 7 arthritis, 8 chronic colitis, 9 esophagitis, 10 thyroiditis, 11 organizing pneumonia, 12 immunoglobulin G4–related disease, 13 SAPHO syndrome, 14 and dermatomyositis 15 has also been reported. In our case, 68 Ga-DOTA-FAPI-04 uptake was significantly increased in radioactive iodine–induced chronic parotitis.…”
mentioning
confidence: 99%
“…68 Ga-FAPI is a potential novel PET agent developed for the detection of a variety of primary tumors and metastatic tumors 1–4 . However, 68 Ga-FAPI also can have obvious accumulation at the sites of inflammatory diseases including cholecystitis, 5 colitis, 6 arthritis, 7 pulmonary cryptococcus, 8 and pancreatitis 9 . Our case indicates that granulomatous inflammation should be considered as one of the possible causes when focal FAPI activity was noted at the site of the orbital mass.…”
mentioning
confidence: 83%
“…4,5 Also, FAPI uptake has been reported in nonmalignant diseases because of the chronic inflammation-induced transformation of fibroblasts to CAFs. [6][7][8][9] Zhang et al 10 showed that H. pylori infection-induced mesenchymal stem cells may transform to CAFs-like cells in gastric mucosa and cause developing of gastric lesions. Another study revealed that, due to chronic inflammation, activated macrophages also cause to the CAFs-like transformation of mesenchymal stem cells.…”
Section: Figurementioning
confidence: 99%